1975
DOI: 10.1073/pnas.72.1.194
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin as a template for RNA synthesis in vitro.

Abstract: RNA transcribed in vitro from myeloblast chromatin by exogenously added RNA polymerase B predominantly consists of short chains that remain in hybrid structure with the template; the remainder of the product is free RNA of heterogeneous size. Addition of polyanions during synthesis caused an increase in the size and amount of free RNA with a concomitant decrease in the proportion of small RNA. The large molecular weight RNA is derived from the short RNA chains, which are synthesized de novo during the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1976
1976
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…Groner et al. (39) found that the greatest part of the RNA synthesized in chromatin isolated from chicken leukemic cells was in the form of RNA-DNA hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Groner et al. (39) found that the greatest part of the RNA synthesized in chromatin isolated from chicken leukemic cells was in the form of RNA-DNA hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Endoge nous ribonuc1eases and RNA polymerases are among these activities. While some workers have reported preparations of chromatin with no detectable RNase activity (27,28), most chromatin preparations contain RNase capable of reducing RNA to fragments of 4 to. 5S.…”
Section: Measurements Of Total Template Capacitymentioning
confidence: 99%
“…A closed complex is sensitive to heparin until a temperature-dependent conformational change occurs to form the open complex (Yarbrough et al, 1976;Carpousis and Gralla, 1980;Hansen and McClure, 1980). In eukaryotic systems, heparin inhibits RNA polymerase II initiation but not elongation (Groner et al, 1975) and inhibits assembly of the RNA polymerase III transcription complex (Logan and Ackerman, 1988).…”
Section: Adriamycinmentioning
confidence: 99%